2010
DOI: 10.1063/1.3464479
|View full text |Cite
|
Sign up to set email alerts
|

Cubic gauche-CN: A superhard metallic compound predicted via first-principles calculations

Abstract: In this paper, we suggest a novel potential superhard material, a new carbon nitride phase consisted of sp(3) hybridized bonds, possessing a cubic P2(1)3 symmetry (8 atoms/cell, labeled by cg-CN) which is similar to cubic gauche nitrogen (cg-N) by first-principles calculations. It is a metallic compound, while most of other superhard materials are insulators or semiconductors. The Vickers hardness of cg-CN is 82.56 GPa, and if we considered the negative effect of metallic component on hardness, it is 54.7 GPa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 53 publications
0
55
0
Order By: Relevance
“…The analysis of our simulation results has confirmed the earlier predicted cg-CN structure. 17 cg-CN was a superhard metallic compound, which was derived from cg-N. 29 Remarkably, we have uncovered seven CN structures never found in previous literature, to the best of our knowledge. They are depicted in Figs.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The analysis of our simulation results has confirmed the earlier predicted cg-CN structure. 17 cg-CN was a superhard metallic compound, which was derived from cg-N. 29 Remarkably, we have uncovered seven CN structures never found in previous literature, to the best of our knowledge. They are depicted in Figs.…”
Section: Resultsmentioning
confidence: 56%
“…GaSe and β-InS CN are energetically favorable and mechanically stable but it is found that these two structures are dynamically unstable at ambient pressure, cg-CN is the most preferential carbon nitride with 1:1 stoichiometry. 17 We have searched for new hard materials based on carbon and nitrogen elements, and attained seven new CN materials with 1:1 stoichiometry predicted by a CALYPSO (crystal structure analysis by particle swarm optimization) structural search technique based on the particle swarm optimization (PSO) algorithm. 18,19 These new seven predicted a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…As in the case of C 3 N 4 , initial theoretical predictions for the CN materials [14][15][16] were based on known structural types of AB compounds like zincblende, rocksalt, body centered tetragonal (bct), etc. Later, a new cg-CN has been proposed [17] as more stable than the previously predicted ones up to ca 100 GPa. A more recent theoretical study [18], based on an advanced structural search algorithm, proposed an orthorhombic Pnnm structure to be the most stable one above ca 10 GPa (which is the stability threshold in respect to carbon and nitrogen) up to 100 GPa, with the highest hardness.…”
mentioning
confidence: 91%
“…Finally, at a very high N%, dt N reduces drastically although there is a small change of dt p , which explains that a stabilized C À N structure can be achieved in C-N films. 34,[37][38][39][40] There are proposals of formation of a stable (crystalline) structure of C À N for high N%. 34,[37][38][39][40] There could be a different hypothesis of dt N vs. dt p , but we wanted to include a general trend, i.e., dt N increasing with dt p and at some stage the behavior is just the opposite.…”
Section: Discussionmentioning
confidence: 98%
“…However, at a very high N concentration disorder decreases sharply as if the sp 2 C structures stabilize. 22,27,28,[37][38][39][40] To resolve this complicated problem, we propose a model of correlated disorder (case (B)) where the distortion of carbon sp 2 structures is correlated with the distortion of incorporated nitrogen. The N doping centers experience some distortion due to interaction with the C atoms.…”
Section: Nitrogen Incorporated Carbon Structurementioning
confidence: 99%